'There is such a thing as too healthy!' The impact of minimum nutritional guidelines on school food practices in secondary schools. Issue 1 (25th September 2018) - Addis, S.; Murphy, S.
Abstract: Background: Pressure to improve school meals has resulted in stringent nutritional guidelines across the UK. In Wales, the 'Appetite for Life' guidelines of 2008 resulted in significant changes to the provision of food in Welsh schools. Although evaluation of these changes has focussed on nutritional quality, there is little evidence of how pupils perceive these changes and their impact on school food practices. Using a Collective Lifestyles approach, the present study reports how secondary school pupils perceive and negotiate menu changes and the implications for lunchtime practices. Methods: Seven focus groups (52 pupils) were undertaken in four secondary schools within one local authority in Wales. Participatory techniques were used to facilitate discussion, and the focus groups were recorded, transcribed and analysed using a framework approach. Analysis was underpinned by a Collective Lifestyles approach, which provides a framework to understand behaviour in context using three domains: (i) patterns of consumption; (ii) the construction and maintenance of identity; and (iii) power relationships. Results: Pupils reported that the new menus were unpopular in terms of content and meal type; the preference was for portable and snack style foods. In terms of power relationships, pupils' ability to negotiate within the school setting was constrained by the institutional nature of school dining. As a result, pupils tended to opt out of school food provision, accessing alternatives where possible. Conclusions: The development of the healthy eating agenda within the school setting needs to consider the complexities of adolescent consumption preferences, identities and social networks if they are to be successful.